The association between serum magnesium and type 2 Diabetes mellitus in adult patients at a tertiary hospital in Malaysia - Hashim, Nurul Hidayah; C. Thambiah, Subashini; Masiman, Ana Daliela; Samsuddin, Intan Nureslyna; Zahari Sham, Siti Yazmin; Osman, Malina; Lai, Yin Ye (Fakulti Perubatan dan Sains Kesihatan, UPM, 2023)
Introduction: Magnesium (Mg) has an important role in glucose metabolism and acts as a cofactor for many enzymatic reactions. However, Mg deficiency frequently goes unnoticed. The aim of this study was to determine the association between serum Mg and type 2 diabetes mellitus (T2DM). Methods: A cross-sectional study was done among T2DM patients who were followed-up at the Diabetic Clinic at Hospital Melaka. Serum Mg test was added to the routine investigations of all patients with diabetes who participated. Results: Prevalence of hypomagnesaemia was 21.5. There was a significant difference in age, duration of T2DM and diabetic complications that include retinopathy, neuropathy, nephropathy, coronary heart disease and cerebrovascular accident as well as all laboratory parameters except high-density lipoprotein cholesterol between the hypomagnesaemia and normomagnesaemia groups. Glycated haemoglobin (HbA1c), fasting plasma glucose and duration of diabetes independently predicted serum Mg levels in T2DM patients. Conclusion: These find- ings support the use of serum Mg as an indirect biomarker of glycaemic control in T2DM patients, whereby hypomagnesaemia indicates poor control.